The Historical Antecedents of Platonism: The Role of the Presocratics According to the Neoplatonists - Motta, Anna (Peitho. Examina Antiqua, 2014)
One of the aims of the Neoplatonists is to demonstrate that ancient Presocratic thought is, in fact, a Preplatonic thought. According to the Neoplatonists, Presocratics, who were not far from the truth, employed an inaccurate and ambiguous language, whereas Plato spoke about the truth in a more appropriate and clear way. That is why the Presocratics are not necessarily erroneous and their theoretical originality and their terminology can be incorporated into the Neoplatonic philosophy. I would like to show how some Presocratic theories are embedded in the Neoplatonic metaphysical system of the three Hypostases. Regarding the One and the Intellect, Plotinus, Proclus and the Anonymous Author of the Prolegomena to Platonic Philosophy read and employ some Presocratic texts in order to harmonize the Platonic and the Presocratic accounts. Although the Neoplatonists see themselves as continuing the Greek philosophical tradition started by the Presocratics, their interpretation of Presocratic thought illustrates the birth of exegetic philosophy which is able to apply ancient concepts and predicates to its own metaphysical theory.